2008
DOI: 10.1007/s00705-008-0080-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient rescue of infectious bursal disease virus using a simplified RNA polymerase II-based reverse genetics strategy

Abstract: We describe a simplified RNA polymerase II-based reverse genetics approach that allows for the efficient rescue of high-titer infectious bursal disease virus (IBDV) from cloned cDNAs of genomic segments A and B. Unlike the previously reported RNA polymerase II-based methods, the developed strategy does not necessitate the introduction of a ribozyme sequence at both ends of the genomic cDNA sequences. This was achieved by fusing the 5' terminal sequence of the cDNA of each segment to the transcription start sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In support of this explanation, we also showed that the in vitrotranscribed and artificially 5= capped IBDV RNA could successfully be translated into viral proteins and rescued into infectious IBDV by itself ( Fig. 5A) and that IBDV could also be efficiently rescued from the capped viral RNAs generated by the RNA polymerase II promoter (37). The defect in virus production and translation of IBDV uncapped RNA imposed by the lack of a 5= cap was rescued by the viral proteins VP1 and VP3 provided in trans, which is in line with previous observations (38).…”
Section: Discussionsupporting
confidence: 64%
“…In support of this explanation, we also showed that the in vitrotranscribed and artificially 5= capped IBDV RNA could successfully be translated into viral proteins and rescued into infectious IBDV by itself ( Fig. 5A) and that IBDV could also be efficiently rescued from the capped viral RNAs generated by the RNA polymerase II promoter (37). The defect in virus production and translation of IBDV uncapped RNA imposed by the lack of a 5= cap was rescued by the viral proteins VP1 and VP3 provided in trans, which is in line with previous observations (38).…”
Section: Discussionsupporting
confidence: 64%
“…Plasmid constructs pVAXSA.Rib and pVAXSB.Rib [ 32 , 33 ] contain the full-length cDNA sequence of the cell culture-adapted and attenuated P2 strain segments A and B, respectively [ 34 ]. In both constructs, the 5′ end of each genomic segment was fused to the transcription start site of the immediate early CMV promoter, while a hepatitis delta virus (HDV) ribozyme sequence was added at the 3′ end.…”
Section: Methodsmentioning
confidence: 99%
“…In both constructs, the 5′ end of each genomic segment was fused to the transcription start site of the immediate early CMV promoter, while a hepatitis delta virus (HDV) ribozyme sequence was added at the 3′ end. This cloning strategy was designed so that the host RNA polymerase II will produce segments A and B transcripts with authentic 5′ and 3′ termini; an in vivo reverse strategy which has significantly improved the titer of rescued IBDV [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations